2012
DOI: 10.1113/expphysiol.2011.061804
|View full text |Cite
|
Sign up to set email alerts
|

Novel targets for sepsis‐induced kidney injury: the glomerular arterioles and the sympathetic nervous system

Abstract: Sepsis and septic shock are the most common causes of acute kidney injury (AKI) in the intensive care unit, and mortality remains high despite improvements in our ability to support vital organs. The lack of development of effective treatments is partly because there has been little advance in our understanding of the pathophysiology of septic AKI, owing to the difficulty in conducting experiments on critically ill patients and use of inappropriate experimental models. Recently, however, a number of new concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 86 publications
(105 reference statements)
1
22
0
1
Order By: Relevance
“…Thus, renal hypoperfusion appears highly unlikely as a cause of septic AKI, given this experimental setting. A recently promoted hypothesis for sepsis-induced AKI is that the inflammatory response causes a preferential dilatation of renal efferent arterioles, increasing renal blood flow but reducing the hydrostatic pressure for glomerular filtration and thereby glomerular filtration rate (GFR) [32]. The most important vasodilator released in sepsis is NO, and it has been suggested that excessive intra-renal NO could be responsible for the reduction in postglomerular resistance [33].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, renal hypoperfusion appears highly unlikely as a cause of septic AKI, given this experimental setting. A recently promoted hypothesis for sepsis-induced AKI is that the inflammatory response causes a preferential dilatation of renal efferent arterioles, increasing renal blood flow but reducing the hydrostatic pressure for glomerular filtration and thereby glomerular filtration rate (GFR) [32]. The most important vasodilator released in sepsis is NO, and it has been suggested that excessive intra-renal NO could be responsible for the reduction in postglomerular resistance [33].…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Recent experimental data from models of hyperdynamic sepsis in sheep questioned this paradigm, and data introduced the concept of decreased rather than increased glomerular vascular resistance, at least in early sepsis in ruminants. 11,12 Although the decline in GFR is mainly attributable to a profound lowering of the intraglomerular capillary pressure, the potential contributions of elevation of Bowman's pressure secondary to tubular obstruction and/or increased tubular flow in hyperfiltrating nephrons, impaired hydraulic permeability, and reduction of filtration surface area should be addressed by other studies in relevant animal models. Collectively, it is conceivable that a comparison of determinants of hypofiltration among progressors and nonprogressors of AKI as well as precise (semi)continuous monitoring of changes in GFR over extended periods of time should allow more sensitive investigations of the role of intrarenal hemodynamics during the development of AKI.…”
Section: Renal Microcirculation Glomerular Hemodynamics In Akimentioning
confidence: 99%
“…10 In contrast to this scenario, glomerular dynamics in the course of septic AKI are controversial. 7,8,11 The widely held concept of a fall in transcapillary hydraulic pressure caused by afferent arteriolar vasoconstriction leading to the reduction in GFR in sepsis has been largely derived from rodents challenged with large endotoxin bolus. 7,8 Recent experimental data from models of hyperdynamic sepsis in sheep questioned this paradigm, and data introduced the concept of decreased rather than increased glomerular vascular resistance, at least in early sepsis in ruminants.…”
Section: Renal Microcirculation Glomerular Hemodynamics In Akimentioning
confidence: 99%
“…En effet, les propriétés pharmacocinétiques et pharmacodynamiques des antibiotiques peuvent être affectées par les modifications physiopathologiques qui accompagnent cet état. Le traitement du choc septique augmente la pression intraglomérulaire et la perméabi-lité capillaire, favorisant un troisième secteur et résultant en une clairance rénale plus élevée [41]. À ce jour, cependant, la réflexion concernant les paramètres pharmacocinétiques est davantage adaptée au traitement des bactériémies.…”
Section: Exemple Des Antibiotiquesunclassified